Studi Literatur: Analisis Faktor-Faktor Nutrisi Yang Memperburuk Akne Vulgaris - Ni Made Ayu Shandy Berliana Putri; Made Budiawan; Ida Ayu Diah Purnama Sari (Jurnal Kesehatan Mahardika, 2025)
Acne vulgaris is a chronic inflammatory skin disorder commonly affecting adolescents and young adults, often leading to decreased self-confidence and quality of life. Its pathogenesis involves hormonal imbalance, bacterial colonization, and environmental influences, including nutrition. This study aims to analyze the nutritional factors that aggravate acne vulgaris through a literature review. Articles were obtained from PubMed, ScienceDirect, and Google Scholar using the keywords “acne vulgaris,” “nutrition,” “diet,” “glycemic index,” “dairy products,” and “inflammation,” limited to studies published between 2015–2025. Out of 48 identified articles, 17 met the inclusion criteria, including observational studies, randomized trials, and systematic reviews discussing the relationship between diet and acne. Results indicate that high-glycemic foods, dairy products, whey protein, and saturated fats exacerbate acne through hormonal and inflammatory mechanisms, while fiber, fruits, vegetables, and omega-3 fatty acids have protective effects. In conclusion, nutrition plays a significant role in acne severity, emphasizing the importance of balanced dietary patterns and nutrition education as supportive strategies for acne management, particularly among adolescents.